STUDY OF FORMATION OF SHFORMATIC COMPETENCIES IN THE FUTURE TEACHERS OF MATHEMATICS (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the study of level of the preparation of the using of the informatics technology of the school-leavers on the physics and mathematics department of the highschool. The groups of the formation’s criteria o f the inform competence are selected by the future teachers of the mathematics.